Analisis Minat Belajar Siswa Pada Pembelajaran Matematika Siswa Kelas 5 Sd N 1 Bebalang - Ni Komang Santi Ulandari; Ni Wayan Sri Darmayanti; I Nyoman Sudirman (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine students' interest in learning mathematics at SD N 1 Bebalang. The question to be answered in this research is: What is students' interest in learning in mathematics at SD N 1 Bebalang. To answer this question, this research uses qualitative research using qualitative descriptive methods. The data collection used was questionnaires, interviews and documentation. Meanwhile, in analyzing the data, researchers used quantitative descriptive analysis techniques. The results of this research are interest in terms of all the indicators that influence being in the interested category. With the percentage of students who were very interested there were 7 people (38.8%), there were 8 students who were interested (44.4%), there were 3 students who were quite interested (16.8%), there were no students who were less interested or not interested (0%). Interest in learning in terms of teacher and student interviews stated that students were included in the category of students interested in participating in mathematics learning.